The Impact of Fireworks Noise on the Acoustic Climate in Urban Areas - Bartłomiej KUKULSKI; Tadeusz WSZOŁEK; Dominik MLECZKO (Archives of Acoustics)
New Year’s Eve is an example of a situation in which urban residents are exposed to an almost continuous and increased noise level from the impulsive sounds sources – fireworks. This custom has become a source of many controversies related to the protection of human and animal health or environmental pollution. However, current legal regulations only slightly affect the subject of noise of fireworks and its harmfulness. Currently, it does not seem possible to completely prohibit the use of fireworks in urban areas, but this does not mean that it is not possible to decrease the degree of their annoyance. The paper consists the issues of identification, analysis and assessment of impulsive noise of fireworks and acoustic climate during New Year’s Eve. Material presented refers to measurements of time series, frequency spectrum and values of noise parameters of selected fireworks. It was presented, among others, that the measured values exceed the criteria for occupational noise (LCpeak), due to the direct hazard of hearing loss, from 1.8 dB at a distance of 25 m and 6.2 dB at a distance of 15 m. Also this work discusses results of impulsive noise measurements of fireworks recorded during New Year’s Eve in years 2016–2017. Material refers to measurements at three measurement points spread over the city of Kraków. Obtained results were compared with typical noise levels for night time in urban area, indicating also the main sources of annoyance and hazard from this type of noise.